'Can you look me in the face?' Short-term SSRI administration reverts avoidant ocular face exploration in subjects at risk for psychopathology. - Di Simplicio, M; Doallo, S; Costoloni, G; Rohenkohl, G; Nobre, A; Harmer, C (2014)
Anxiety and depression are associated with altered ocular exploration of facial stimuli, which could have a role in the misinterpretation of ambiguous emotional stimuli. However, it is unknown whether a similar pattern is seen in individuals at risk for psychopathology and whether this can be modified by pharmacological interventions used in these disorders. In Study 1, eye gaze movement during face discrimination was compared in volunteers with high vs low neuroticism scores on the Eysenck Personality Questionnaire. Facial stimuli either displayed a neutral, happy, or fearful expression. In Study 2, volunteers with high neuroticism were randomized in a double-blind design to receive the selective serotonin reuptake inhibitor citalopram (20 mg) or placebo for 7 days. On the last day of treatment, eye gaze movement during face presentation and the recognition of different emotional expressions was assessed. In Study 1, highly neurotic volunteers showed reduced eye gaze towards the eyes vs mouth region of the face compared with low neurotic volunteers. In Study 2, citalopram increased gaze maintenance over the face stimuli compared with placebo and enhanced recognition of positive vs negative facial expressions. Longer ocular exploration of happy faces correlated positively with recognition of positive emotions. Individuals at risk for psychopathology presented an avoidant pattern of ocular exploration of faces. Short-term SSRI administration reversed this bias before any mood or anxiety changes. This treatment effect may improve the capacity to scan social stimuli and contribute to the remediation of clinical symptoms related to interpersonal difficulties.